Low-glucose conditions of tumor microenvironment enhance cytotoxicity of tetrathiomolybdate to neuroblastoma cells - Navrátilová, Jarmila; Hankeová, Tereza; Beneš, Petr; Smarda, Jan (Nutrition and cancer, 2013)
Growth of tumor cells depends on sufficient supply of fermentable substrate, such as glucose. This provokes development of new anticancer therapies based on dietary restrictions. However, some tumor cells can lower their glucose dependency and activate processes of ATP formation/saving to retain viability even in limited glucose supply. In addition, tumor cells often lose sensitivity to many conventional anticancer drugs in the low-glucose conditions. Thus, development of the drugs effectively killing the tumor cells in nutrient-limited conditions is necessary. In this study, we show an enhanced cytotoxicity of tetrathiomolybdate, the drug exhibiting antiangiogenic and tumor-suppressing effects, to neuroblastoma SH-SY5Y and SK-N-BE(2) cells in the low-glucose conditions. This preference results from the tetrathiomolybdate-induced upregulation of cell dependency on glucose. The cells treated with tetrathiomolybdate increase the uptake of glucose, production of lactate, activate the Akt- and AMPK-signaling pathways and downregulate COX IV. In cells growing in the low-glucose conditions, these events result in significant decrease of the intracellular ATP supply and apoptosis. We propose tetrathiomolybdate as suitable agent to be used in combination with dietary restrictions in therapy of neuroblastoma.
Keywords: Cell Survival; signální transdukce; Signal Transduction; inhibitory angiogeneze; Humans; neuroblastom; Down-Regulation; molybden; viabilita buněk; Hypoxia; proteinkinasy aktivované AMP; lidé; proliferace buněk; glukosa; down regulace; AMP-Activated Protein Kinases; apoptóza; hypoxie; protoonkogenní proteiny c-akt; Proto-Oncogene Proteins c-akt; Molybdenum; Cell Proliferation; Glucose; Angiogenesis Inhibitors; Tumor Microenvironment; nádorové buněčné linie; nádorové mikroprostředí; Neuroblastoma; Cell Line, Tumor; Apoptosis